Post-treatment haemolysis in African children with hyperparasitaemic falciparum malaria; a randomized comparison of artesunate and quinine - Fanello, C; Onyamboko, M; Lee, S; Woodrow, C; Setaphan, S; Chotivanich, K; Buffet, P; Jauréguiberry, S; Rockett, K; Stepniewska, K; Day, N; White, N; et al. (BioMed Central, 2017)
Background Parenteral artesunate is the treatment of choice for severe malaria. Recently, haemolytic anaemia occurring 1 to 3 weeks after artesunate treatment of falciparum malaria has been reported in returning travellers in temperate countries. Methods To assess these potential safety concerns in African children, in whom most deaths from malaria occur, an open-labelled, randomized controlled trial was conducted in Kinshasa, Democratic Republic of Congo. 217 children aged between 6 months and 14 years with acute uncomplicated falciparum malaria and parasite densities over 100,000/μL were randomly allocated to intravenous artesunate or quinine, hospitalized for 3 days and then followed for 42 days. Results The immediate reduction in haemoglobin was less with artesunate than with quinine: median (IQR) fall at 72 h 1.4 g/dL (0.90–1.95) vs. 1.7 g/dL (1.10–2.40) (p = 0.009). This was explained by greater pitting then recirculation of once infected erythrocytes. Only 5% of patients (in both groups) had a ≥ 10% reduction in haemoglobin after day 7 (p = 0.1). One artesunate treated patient with suspected concomitant sepsis had a protracted clinical course and required a blood transfusion on day 14. Conclusions Clinically significant delayed haemolysis following parenteral artesunate is uncommon in African children hospitalised with acute falciparum malaria and high parasitaemias.